Linguistics Devices’ Appreciation in Semarang’s Online Cuisine Advertisement Text - Nanik Setyawati; Riyadi Santosa; Sumarlam Sumarlam; Dwi Purnanto (Universitas Cokroaminoto Palopo, 2020)
Persuasive communication can be found in advertisement language. Creating advertisement that attractive, right on target, and effective in attracting potential customers, is a must to win the competition. An advertisement must be able to present everything that is smart, innovative, and must also be different in a unique sense compared to the others. This article specifically explores the appreciation devices in Semarang’s cuisine advertisement text phasing on the internet. Appreciation is one of the choices from the attitude aspects that part of appraisal system. Data in the form of attitudinal lexis were collected from online advertising texts which promote foods in Semarang. The method of providing data using the observation method. The basic technique used is the tapping technique. Meanwhile, the advance techniques used are the free, active, proficient listening technique and the note – taking technique. The data analysis in this study used a separate method. The basic technique used is the technique for direct elements, while the advance technique uses the lesion technique and the dressing technique. The results of the discussion show that the appreciation used in the Semarang’s cuisine advertisement texts on the internet is positive appreciation.